Fuzzy multicriteria flight gate assignment - Andreas Drexl; Yury Nikulin (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2006)
This paper addresses the multiple criteria flight gate assignment problem under uncertainty, which is naturally modeled by fuzzy numbers. The problem examined is a special kind of multicriteria multi-mode resource-constrained project scheduling problem with generalized precedence constraints or time windows. Fuzziness is introduced for basic problem parameters, that is, arrival and departure times, in order to cover possible earliness and tardiness of flights. We solve the problem directly by a special multicriteria metaheuristic, known as fuzzy Pareto simulated annealing, in order to get a representative approximation of the Pareto front.
Keywords: 650; flight gate assignment; multicriteria optimization; project scheduling; Pareto simulated annealing; fuzziness; Flughafen; Multikriterielle Entscheidungsanalyse; Fuzzy-Set-Theorie; Theorie